Development of security mechanisms for scada systems in the postquantium period - Воропай, О. В.; Погасій, С. С.; Король, О. Г.; Мілевський, С. В. (Sistemi obrobki ìnformacìï, 2022)
The formation of new systems based on the synthesis of mobile Internet technologies with cyberspace significantly expands the possibilities of creating smart technologies based on mesh and sensor networks. This allows to significantly increase the speed of information transmission using modern wireless communication channels based on technology standards IEEE802.16, IEEE802.16e, IEEE802.15.4, IEEE802.11, Bluetooth 5, 6. It is possible to use SCADA automation and scheduling systems with new functions of managing information flows of various technological processes, to create new principles for building hyperphysical social systems (CPSS) – a set of subjects and objects of cybernetic, physical and social worlds that allow to form “smart” communities, on the one hand , and intellectual space on the other. However, the development of modern computer systems, the advent of full-scale quantum computers significantly impairs the security of modern security systems. According to NIST experts, a full-scale quantum computer breaks both symmetric and asymmetric cryptosystems in polynomial time, which significantly reduces their stability. The goal of the work is to develop mechanisms for providing security services based on post-quantum algorithms - crypto-code constructions. To ensure security in the post-quantum period – the emergence of a full-scale quantum computer, NIST specialists suggest the use of post-quantum algorithms. Structural schemes of crypto-code constructions of McEliece and Niederreiter on algebrogeometric codes are used in the work. The paper proposes mechanisms of post-quantum cryptography, which allow to ensure the stability of not only communication channels, but also elements of the structure of the management system of SCADA systems, not only in critical infrastructure, but also in modern wireless communication channels. The basis of post-quantum encryption algorithms is the combination of algorithms (schemes) of crypto-code structures with cryptosystems on unprofitable codes (multi-channel cryptography), as well as the possibility of combining them with digital steganography methods. The developed approach provides the ability to hide elements of management commands, and the use of different channels provides the ability to hide individual elements of cryptograms. The use of post-quantum encryption algorithms provides a significant increase in the cryptographic stability of security mechanisms SCADA-systems.